2020
DOI: 10.2139/ssrn.3735967
|View full text |Cite
|
Sign up to set email alerts
|

School’s Out: Experimental Evidence on Limiting Learning Loss Using 'Low-Tech' in a Pandemic

Abstract: Schools closed extensively during the COVID-19 pandemic and occur in other settings, such as teacher strikes and natural disasters. This paper provides some of the first experimental evidence on strategies to minimize learning loss when schools close. We run a randomized trial of lowtechnology interventions -SMS messages and phone calls -with parents to support their child. The combined treatment cost-effectively improves learning by 0.12 standard deviations. We develop remote assessment innovations, which sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…Where this is not possible, individualized online tutoring should be provided. For example, studies conducted during the lockdown in Botswana and Italy have shown that individual online tutoring directly targeting either parents or students in middle school has a positive impact on the achievement of students, particularly for working-class students 122,123 .…”
Section: Practical Recommendationsmentioning
confidence: 99%
“…Where this is not possible, individualized online tutoring should be provided. For example, studies conducted during the lockdown in Botswana and Italy have shown that individual online tutoring directly targeting either parents or students in middle school has a positive impact on the achievement of students, particularly for working-class students 122,123 .…”
Section: Practical Recommendationsmentioning
confidence: 99%
“…To the best of our knowledge, very few policy experiments have attempted to use remote tools to improve learning outcomes during the pandemic. Angrist et al (2020) evaluate two low-tech interventions in Botswana that use SMS text messages and direct phone calls to support parents in the education of their children. The combined intervention resulted in a 0.12 SD improvement in student outcomes and led parents to update their beliefs about their children's learning level.…”
Section: Introductionmentioning
confidence: 99%
“…While performance among children with a higher socioeconomic position continues to improve at times when school is not in session (such as summer vacations), no such improvement is found among children with a lower socioeconomic status (Di Pietro et al, 2020;Haeck & Lefebvre, 2020). To compensate for lost learning in the absence of school, high-income families have access to alternate forms of instruction-books, computers, the Internet, radio, television, and smartphones-that many low-income families do not (Angrist et al, 2020a;Bacher-Hicks et al, 2021).…”
Section: Opportunities To Reach Educationmentioning
confidence: 99%